PENGEMBANGAN WEBSITE PERPUSTAKAAN DIGITAL DI SDN KENDANGSARI I/276 SURABAYA - Vitachurrohma Ahsanu Amalah; Windasari (Edu Learning : Journal of Education and Learning, 2022)
Abstract This study aims to determine the results and validity of the development of a digital library website at SDN Kendangsari I/276 Surabaya. This Research and Development is considered important because developments are needed in the operation of library services in an educational institution considering that currently technological advances cannot be avoided. For this reason, the development of digital libraries in schools must be carried out in order to improve the quality of services provided at an educational institution. This research is a type of Research and Development (R&D) method using the waterfall development model in its stages. In this case, to measure the validity of the website, research subjects are needed consisting of: design experts, material experts, and a sample of 30 people determined by cluster sampling from SDN Kendangsari I/276 Surabaya. The data collection technique uses a questionnaire distribution to validate the use of the website which then the results of the data are analyzed descriptively as statistics. The results showed that the percentage achievement of design experts was 72% with high validity criteria and material experts was 98% with very high validity criteria, so it was feasible to be tested. The results of the small group trial were 83.57% and the large group trial was 96.73% which can be concluded that most users were satisfied in using the digital library website.